Model Decision Tree Analysis dalam Penerapan Manajemen Risiko Studi Kasus: Webinar Kerja, Kerja, Tipes! pada Tahun 2021 oleh Seemore Event Organizer - Nadya Dwi Yanti (Bisnis Event, 2023)
During the COVID-19 pandemic, event organizing activities in Indonesia switched from the concept of being online (virtual). The virtual event activities that were rife at that time were online seminars or webinars with different themes and speakers. In December 2021, Seemore Event Organizer in collaboration with a psychology consulting company called Arsanara has also successfully held a webinar event with the theme of toxic productivity in the world of work entitled "Work, Work, Types!" presenting participants of more than 50 people. Even though the implementation of this activity is virtual, it does not avoid the possibility of risks, especially in the scope of program activities and event operations. Seeing this, the researcher who serves as the coordinator of the program division uses the decision tree analysis model as a reference in making decisions to minimize the impact of risks that might occur in the event. From the research conducted, there are 5 types of risks from the program and operational fields which can be detailed with a decision tree model to choose 2 alternative decisions that can be made as prevention or mitigation of a risk. In its application, alternatives are needed (what can be done), costs (price to be paid), and benefits (the impact of each alternative chosen). The decision tree analysis model can help to analyze the factors and impacts resulting from each alternative decision on a risk that can be taken by policy makers with the aim of avoiding or minimizing the impact of risks that will occur.